Mitochondrial MicroRNAs Contribute to Macrophage Immune Functions Including Differentiation, Polarization, and Activation - Duroux-Richard, Isabelle; Apparailly, Florence; Khoury, Maroun (Frontiers in Physiology, 2021)
A subset of microRNA (miRNA) has been shown to play an important role in mitochondrial (mt) functions and are named MitomiR. They are present within or associated with mitochondria. Most of the mitochondrial miRNAs originate from the nucleus, while a very limited number is encoded by mtDNA. Moreover, the miRNA machinery including the Dicer and Argonaute has also been detected within mitochondria. Literature has well stablished a close relationship between miRNAs and inflammation. Indeed, specific miRNA signatures are associated with macrophage differentiation, polarization and functions. Nevertheless, the regulation of macrophage inflammatory pathways governed specifically by MitomiR and their implication in immune-mediated inflammatory disorders remain poorly studied. Here, we propose a hypothesis in which MitomiR play a key role in triggering macrophage differentiation and modulating their downstream activation and immune functions. We sustain this proposition by bioinformatic data obtained from either the human monocytic THP1 cell line or the purified mitochondrial fraction of PMA-induced human macrophages. Interestingly, 22% of the 754 assayed miRNAs were detected in the mitochondrial fraction, and are either exclusively or highly enriched cellular miRNA. Furthermore, our in-silico analyses identified a specific MitomiR signature associated with macrophage differentiation and correlated with gene targets within the mitochondria genome or with mitochondrial pathways. Overall, our hypothesis and data suggest a previously unrecognized link between MitomiR and macrophage function and fate. We also suggest that this MitomiR-dependent control could be further enhanced through the transfer of mitochondria from donor to target cells, as a new strategy for MitomiR delivery.